Răspuns :
Inseamna ca a/5 = b/7 = k => a=5k si b=7k
inlocuim in relatia a doua ... (5k+5)/(7k+1) = (5k+7k)/(7k+10}
⇵
(5k+5)(7k+10)=(5k+7)(7k+1)
35k²+35k+50k+50=35k²+49k+5k+7
35k+50k-49k-5k=7-50
31k = 43 => k=43/31
=> a=5 * 43/31 = 215/31 si b=7 * 43/31 =301/31
inlocuim in relatia a doua ... (5k+5)/(7k+1) = (5k+7k)/(7k+10}
⇵
(5k+5)(7k+10)=(5k+7)(7k+1)
35k²+35k+50k+50=35k²+49k+5k+7
35k+50k-49k-5k=7-50
31k = 43 => k=43/31
=> a=5 * 43/31 = 215/31 si b=7 * 43/31 =301/31
a/5 = b/7 = (a + b)/12 = k a= 5k b = 7k a + b = 12k
(a + 5)/(b +1) = (a + b)/(b + 10)
(5k + 5)/(7k+1) = 12k/(7k + 10)
(5k+5)(7k+10) = 12k(7k+1)
35k² + 85k + 50 = 84k² + 12k
49k² - 73k - 50 = 0 49k² - 98k + 25k - 50 = 0 49k(k - 2) + 25(k-2) = 0
(k-2)(49k + 25) = 0 k - 2 = 0 k = 2
a = 10 b = 14
(a + 5)/(b +1) = (a + b)/(b + 10)
(5k + 5)/(7k+1) = 12k/(7k + 10)
(5k+5)(7k+10) = 12k(7k+1)
35k² + 85k + 50 = 84k² + 12k
49k² - 73k - 50 = 0 49k² - 98k + 25k - 50 = 0 49k(k - 2) + 25(k-2) = 0
(k-2)(49k + 25) = 0 k - 2 = 0 k = 2
a = 10 b = 14